Toksisitas Subkronis Timbal (Pb) dalam Limbah Padat IPAL Industri Kertas terhadap Karakteristik Darah Tikus Rattus norvegicus - Rina S Soetopo; Ahmad Ridwan; Suripto Suripto (Center for Pulp and Paper, 2008)
The primary environmental problem associated with open dumping solid waste disposal is the leachate potency to contaminates ground and surface waters. Paper industry solid waste using mixture raw material with deinked pulp is contaminated by heavy metals. One of the heavy metals is lead (Pb) which is dominant in waste. The effects of subchronic toxicity of paper solid waste to blood characteristics of rat (Rattus norvegicus) have been done. Solid waste extract was administered to each individual rat by gavage through gastrointestinal tract at three different doses (350; 2500 and 5000 mg/kg body weight/day) and also positif control (0,5; 5,0; 50; 500; 5000 µg/kg body weight/day) and negatif control (water) daily during 90 days period. Results showed that subchronic toxicity effect of lead in 5000 μg/kg body weight/day of paper industry solid waste caused reduction to blood δ-ALA-D activities, hemoglobin concentration and hematocrit value, but it was still in normal ranges.